AKUNTANSI INTERNASIONAL: PENGARUH BUDAYA TERHADAP SISTEM AKUNTANSI - Ilham Z. Salle (Jurnal Manajemen Lakidende: Economic & Business, 2020)
International accounting is accounting for international transactions. The environment in which the company operates will have an impact on financial reporting and disclosure. One aspect of the environment is culture. Culture is the most powerful environmental factor affecting a country's accounting system as well as how individuals in that country use accounting information. Cultural influence on the accounting system is an issue that many academics and practitioners talk about. Even the issue concerns whether culture affects accounting or vice versa. Many experts offer cultural and accounting relationship theory frameworks such as Gray and Hofstede. Tests on the framework of this theory have also been done a lot. The test results concluded the results were mixed but overall the framework of Gray and Hofstede theory is still relevant even useful in designing international accounting standards in addition to being used by investors in mapping cultures and disclosures in various countries.